Exploring perfluoroalkyl substances contamination in human breast milk: First ghanaian study - Justice Wiston Amstrong Jonathan; David K. Essumang; John K. Bentum; Daniel Elorm Kwame Kabotso; Innocentia Ruby Gborgblorvor; Albert Eshun; Norkplim Dei Hlorlewu; Elizabeth Davordzi (Chemosphere, 2024)

Development and preliminary validation of a modified Food Craving Inventory for Pregnancy (FCI-P) in U.S. military active-duty Service women - Katherine Thompson; Marney A. White; Ruby Schrag; Jason M. Lavender; Viviana Bauman; Autumn Mains; Stephanie Rioux; Holly Spinner; Isabel Thorstad; David Klein; Mark Haigney; Marian Tanofsky-Kraff (Appetite, 2024)

Peer-to-peer exchanges on island resilience planning for transformative adaptation to climate hazards - Laura Brewington; Victoria W. Keener; Kaʻāina Hull; Ruby Pap; Marie Williams (Ocean & Coastal Management, 2024)

Environmental assessment of green wall: A comparison between Australia and Italy - Milad Reyhani; Enrica Santolini; Ruby N. Michael; Alberto Barbaresi; Patrizia Tassinari; Daniele Torreggiani (Science of The Total Environment, 2024)

In-field carbon dioxide removal via weathering of crushed basalt applied to acidic tropical agricultural soil - Fredrick J. Holden; Kalu Davies; Michael I. Bird; Ruby Hume; Hannah Green; David J. Beerling; Paul N. Nelson (Science of The Total Environment, 2024)

Corrigendum to “Recycled waste substrates: A systematic review” [Sci. Total Environ. 953 (2024) (25 November 2024) 176029] - Shuraik Kader; Ivan Gratchev; Ruby N. Michael (Science of The Total Environment, 2024)

Population dynamics of the black mussel Mytella strigata (Hanley, 1843) across environmental gradients in Panguil Bay, Philippines: Implications for management - Kaent Immanuel N. Uba; Robert Keith A. Sienes; Hessed T. Cabanilla; Paz Geneveve Q. Gacus; Michael H. Flores; Ruby C. Gonzales; Junaisah Nissi L. Degoma; Delyn M. Bucay (Regional Studies in Marine Science, 2024)

Gradient of acid mine drainage regulates microbial community assembly and the diversity of species associated with native plants - Qinhong Cai; Chinedu C. Obieze; Ruby Pyke; Karine Delorme; Christine Maynard; Charles W. Greer; Damase Khasa (Environmental Pollution, 2024)

Nutrients monitoring on the Bui multipurpose dam project in the Savannah region of Ghana - Jacob Asomaning; Cynthia Laar; Crentsil Kofi Bempah; Godfred Ayanu; John Senu; Ruby Eshun; George Crabbe; Eric Ofosu Antwi (Environmental Nanotechnology, Monitoring & Management, 2024)

Aerobic thermophilic digestion of fecal matter: Condensate recovery, low solids production, and water reuse - Ruby A. Lai; Sung-Geun Woo; Emir Aksüyek; Latifah Hamzah; Santiago Alvillar; Kartik Chandran; Craig S. Criddle (Bioresource Technology Reports, 2024)

The tale of tapetum: from anther walls to pollen wall - Ruby Biswas; Shubho Chaudhuri (The Nucleus, 2024)

Two-Stage Polsar Scattering Model-Based Classification Scheme for Improved Glacier Facies Mapping - Ruby Panwar; Amit Kumar; Praveen Kumar (Journal of the Indian Society of Remote Sensing, 2024)

Predicting Soil Organic Carbon in Forest Soils of Telangana, India: A Comparative Analysis of Deterministic and Geostatistical Interpolation Models - Ruby Patel; Shaik Sharief; Sherline; Avinash Kodchire; Vijender Pal Panwar (Journal of Soil Science and Plant Nutrition, 2024)

AtHMGB15 regulates tapetal apoptosis in pollen development and actin dynamics during pollen germination in arabidopsis - Ruby Biswas; Shubho Chaudhuri (Plant Reproduction, 2024)

Recycled waste substrates: A systematic review - Shuraik Kader; Ivan Gratchev; Ruby N. Michael (Science of The Total Environment, 2024)

A new approach to the calculation of variable tangent bending stiffness for helical strands - Liming Gong; Lingzhi Wang; Zhitao Yan; Xiaogang Yang; Yujie Zeng; Ruby Aslam (Ocean Engineering, 2024)

A mathematical model of melatonin synthesis and interactions with the circadian clock - Janet Best; Ruby Kim; Michael Reed; H. Frederik Nijhout (Mathematical Biosciences, 2024)

Seasonal delay of Sahelian rainfall driven by an east–west contrast in radiative forcing in idealized CESM experiments - Hongqiang Dong; Fengfei Song; Fukai Liu; Hai Wang; Lu Dong; L. Ruby Leung; Jian Lu (Climate Dynamics, 2024)

Influence of raceway based biofloc system on the growth and physiological responses of Penaeus vannamei and GIF tilapia in a polyculture model – BFT aquaculture system - M Joshna; Ahilan B; Cheryl Antony; Ravaneswaran K; Chidambaram P; Uma A; Ruby P; Prabu E; Somu Sunder Lingam R (Aquacultural Engineering, 2024)

Effect of environmental air pollutants on placental function and pregnancy outcomes: a molecular insight - Sunil Singh; Isha Goel; Smita Tripathi; Ashok Ahirwar; Megha Kumar; Anubhuti Rana; Ruby Dhar; Subhradip Karmakar (Environmental Science and Pollution Research, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Soil amendments reduce PFAS bioaccumulation in Eisenia fetida following exposure to AFFF-impacted soil - Tanya Cáceres; Ruby Jones; Farzana Kastury; Albert L. Juhasz (Environmental Pollution, 2024)

Membrane distillation-crystallization applied to a multi-ion hypersaline lithium brine for water recovery and crystallization of potassium and magnesium salts - Michelle Quilaqueo; Gabriel Seriche; Carol González; Gianni Piaggio; Lorena Barros; Fred Gallardo; Simón Díaz-Quezada; Daniel Zamora; Belén Barraza; René Ruby-Figueroa; Sergio Santoro; Efrem Curcio; et al. (Desalination, 2024)

CSIDRS – stable isotope data reduction software for the CAMECA LG SIMS - Ruby C. Marsden; Laure Martin; Matvei Aleshin; Paul Guagliardo (Computers & Geosciences, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Patient Education Materials for Immobilisation Masks in Radiation Therapy for Adult Head and Neck Cancer Patients: A Scoping Review - Lucy Wood; Ruby Holman; Uyen Nguyen; Helen Nguyen; Aurora Senaratna; Misha Adams; Apajok Apath (Journal of Cancer Education, 2024)
Immobilisation masks (IMs) are used for people with head and neck cancer (HNC) undergoing radiation therapy (RT) treatment to ensure accuracy and reproducibility between treatments. Claustrophobia-related mask anxiety in HNC patients is common and can compromise treatment due to patient distress. This scoping review aimed to describe the content of publicly available Patient Education Materials (PEMs) for people with HNC undergoing RT. Three search engines (Bing, Yahoo, and Google) were systematically searched using standard terms. PEMs in audio-visual or written formats were eligible for inclusion if the target readership was adults with HNC and included content on IMs for RT. Content was appraised using the Patient Education Materials Assessment Tool for Printable and Audio-Visual Materials to assess understandability and actionability. In total, 304 PEMs were identified of which 20 met the inclusion criteria. Sixteen PEMs were webpages, three were PDF format, and one was a standalone video. The understandability and actionability of PEMs ranged between 47 to 100% and 0 to 80%, respectively. PEMs authored by Foundations/Organisations scored higher in understandability (80–100%) and were more likely to discuss mask anxiety coping strategies. In comparison, News sites and IM manufacturers published PEMs with the lowest understandability scores (20–80%). The significant variations in the quality of IM PEMs identified suggest that some sources may be more effective at informing patients about IMs. Although multiple aspects of the PEMs were consistent across the reviewed materials, many PEMs lacked information, and a stronger focus on understandability and actionability is required.

Synergistic neuromodulation therapy for persistent spinal pain: a proof-of-concept trial on the use of spinal cord and dorsal root ganglion stimulation - Augusto Müller Fiedler; Guilherme Santos Piedade; Bernardo Assumpção de Monaco; Ruby Rose Taylor; Michelle Dawn Williams; John L. Danny; Adrienne Minor; Joacir Graciolli Cordeiro (Acta Neurologica Belgica, 2024)

How the Resist-Accept-Direct framework is being used by communities for socio-economic climate adaptation: a case study in Australia’s Murray-Darling Basin - Ruby C. Olsson; Carina A. Wyborn; Lorrae E. van Kerkhoff (Regional Environmental Change, 2024)
Globally, water governance struggles to reconcile increased demands on water resources with climate change–induced reductions in supply, making climate adaptation in water governance a pressing concern. The Resist-Accept-Direct (RAD) framework has emerged as a climate adaptation tool designed to help make adaptation decisions. However, there is limited understanding of social and political factors, which are critical in driving RAD decisions. This paper explores how communities are employing RAD to make climate adaptation decisions, using a case study of the Goulburn-Murray Resilience Strategy (the Strategy); a community-led strategy that uses a version of the RAD framework to build regional resilience in the Goulburn-Murray Irrigation District (GMID) in Australia’s Murray-Darling Basin (MDB). The Strategy focuses on building socio-economic, rather than ecological, resilience, making this research a valuable contribution to RAD literature. To apply the RAD framework to socio-economic adaptation, we adapted the framework to include IPCC language around incremental, transformational, planned, and autonomous adaptation. With the GMID considered a leader of resilience thinking in Australia, the Strategy may help decision-makers address water overallocation and contested governance in the MDB, and provide lessons for water governance globally. Data analysed from 20 semi-structured interviews with people involved with the Strategy revealed two main findings: (1) Communities and governments prioritise different actions under the RAD framework. Governments, particularly at the state level, preference incremental planned adaptation to maintain the status quo (resist), over incremental autonomous adaptation to changing conditions (accept), and transformational planned adaptation at various scales (direct). (2) Community and government actors perceive that factors driving governments’ preference for incremental-resist adaptation include electoral short-termism, linear planning, and conservative government culture.

Spatiotemporal Shift of Soil Microbes in Conservation Agriculture under a Rice-Based Cropping System at the New Alluvial Zone of Lower Gangetic Plain - Puja Singh; Susanta Dutta; Siddhartha Mukherjee; Niharendu Saha; Bishnuprasad Dash; Samrat Ghosh; Biswabara Sahu; Ruby Pate; Ahana Dey; M Jaison; Tufleuddin Biswas; Biswapati Mandal (Journal of Soil Science and Plant Nutrition, 2024)

Immunomodulation and Humoral Immune Response in Teleost Immunized with Aeromonas-Derived Antigenic Extracellular Bioactive Molecules - Patrick Senam Kofi Fatsi; Koichiro Kawai; Ruby Asmah; Betty Bandoh Oppong; Ebenezer Koranteng Appiah; Shaharior Hashem; Acheampong Addo; Joyce Kplorla Kusorgbor; Emmanuel Kaboja Magna; Abraham Kusi Obeng; Lydia Quansah; Courage Kosi Setsoafia Saba; et al. (Indian Journal of Microbiology, 2024)

Seagrass cover and associated macrobenthic marine invertebrates in Southern Philippines - Dan Arriesgado; Elgen Arriesgado; Elnor Roa; Aida Perpetua; Ruby Gonzales; Rodrigo Acuña; Rustan Eballe; Delyn Bucay; Mayenne Balaba; Lyndon Roa; Bopp Benjack Janolino; Richard Muallil; et al. (Aquatic Ecology, 2024)

Sulfur mitigates lead toxicity through phytochelatin-driven vacuolar sequestration and antioxidant defense in mustard (Brassica juncea) - Ruby Bagchi; MD. Arifuzzaman; MD. Atikur Rahman; Ahmad Humayan Kabir; MD. Sarwar Parvez (Biologia, 2024)

Diet and Dietary Acculturation Among Immigrants From Sub-Saharan Africa Living in the United States: A Scoping Review - Luyue Zheng; Tamara Alam; Amber Khemlani; Ruby Armah; Margrethe Horlyck-Romanovsky (Journal of Nutrition Education and Behavior, 2024)

The first ensemble of kilometer-scale simulations of a hydrological year over the third pole - Emily Collier; Nikolina Ban; Niklas Richter; Bodo Ahrens; Deliang Chen; Xingchao Chen; Hui-Wen Lai; Ruby Leung; Lu Li; Alzbeta Medvedova; Tinghai Ou; Praveen Kumar Pothapakula; et al. (Climate Dynamics, 2024)
An accurate understanding of the current and future water cycle over the Third Pole is of great societal importance, given the role this region plays as a water tower for densely populated areas downstream. An emerging and promising approach for skillful climate assessments over regions of complex terrain is kilometer-scale climate modeling. As a foundational step towards such simulations over the Third Pole, we present a multi-model and multi-physics ensemble of kilometer-scale regional simulations for the hydrological year of October 2019 to September 2020. The ensemble consists of 13 simulations performed by an international consortium of 10 research groups, configured with a horizontal grid spacing ranging from 2.2 to 4 km covering all of the Third Pole region. These simulations are driven by ERA5 and are part of a Coordinated Regional Climate Downscaling EXperiment Flagship Pilot Study on Convection-Permitting Third Pole. The simulations are compared against available gridded and in-situ observations and remote-sensing data, to assess the performance and spread of the model ensemble compared to the driving reanalysis during the cold and warm seasons. Although ensemble evaluation is hindered by large differences between the gridded precipitation datasets used as a reference over this region, we show that the ensemble improves on many warm-season precipitation metrics compared with ERA5, including most wet-day and hour statistics, and also adds value in the representation of wet spells in both seasons. As such, the ensemble will provide an invaluable resource for future improvements in the process understanding of the hydroclimate of this remote but important region.

Current Trends and Innovative Approaches in Cancer Immunotherapy - Jaechang Kim; Ruby Maharjan; Jonghyuck Park (AAPS PharmSciTech, 2024)

When outsiders are resource users: Fishers’ migration in Southwest Panay, Philippines, and its impact on small-scale fisheries - Liberty N. Espectato; Ruby P. Napata; Juhn Chris Espia; Alice Prieto-Carolino (Ocean & Coastal Management, 2024)

Prenatal exposure to polycyclic aromatic hydrocarbons and executive functions at school age: Results from a combined cohort study - Yu Ni; Adam A. Szpiro; Christine T. Loftus; Tomomi Workman; Alexis Sullivan; Erin R. Wallace; Anne M. Riederer; Drew B. Day; Laura E. Murphy; Ruby H.N. Nguyen; Sheela Sathyanarayana; Emily S. Barrett; et al. (International Journal of Hygiene and Environmental Health, 2024)

A Systematic Review of Oceanic-Atmospheric Variations and Coastal Erosion in Continental Latin America: Historical Trends, Future Projections, and Management Challenges - Ruby Vallarino-Castillo; Vicente Negro-Valdecantos; José María del Campo (Journal of Marine Science and Engineering, 2024)
The intricate interplay of oceanic-atmospheric variations has intensified erosive processes on sandy beaches in recent decades, with climate change expected to exacerbate these impacts in the future. Projections for the southern Atlantic and Pacific regions of continental Latin America predict increased extreme events and heightened impacts on sandy beaches, highlighting disparities in studies addressing coastal erosion and its causes. To address these risks, a systematic review is proposed to analyze historical trends and projections, aiming to inform local-level studies and management strategies for at-risk coastal communities. Reviewing 130 research papers, insights reveal the influence of climatic events like El Niño and La Niña on coastal dynamics, as well as the effects of storm intensification and extreme events such as high-intensity waves and storm surges on Latin American coasts, resulting in ecosystem, economic, and infrastructure losses. Projections indicate a rise in the population inhabiting Low Elevation Coastal Zones (LECZ) by the century’s end, emphasizing the urgent need for effective management and planning. Community engagement in erosion monitoring and adaptation programs is crucial for addressing these challenges and developing robust, sustainable, long-term adaptation strategies. This study aims to enhance the understanding of coastal erosion in Latin American communities addressing future coastal risks.

Vegetarian, vegan, or plant-based? Comparing how different labels influence consumer evaluations of plant-based foods - Matthew B. Ruby; João Graça; Eero Olli (Appetite, 2024)

Bio-based ionic liquid as a corrosion inhibitor for mild steel in 5% HCl solution: Experimental and theoretical investigation - Ruby Aslam; Jinmei Zhao; Xiaofeng Sun; Xing Zhou; Qihui Wang; Jeenat Aslam; Zhitao Yan (Sustainable Chemistry and Pharmacy, 2024)

Impacts of aluminum-cerium alloy deployment on different cerium commodities - Michael H. Severson; Ruby T. Nguyen; Adam Sibal; Haeyeon Kim (Resources, Conservation and Recycling, 2024)

Using mid-infrared spectroscopy as a tool to monitor responses of acidic soil properties to liming: case study from a dryland agricultural soil trial site in South Australia - Ruby Hume; Petra Marschner; Sean Mason; Rhiannon K. Schilling; Luke M. Mosley (Precision Agriculture, 2024)
Soil acidification is an issue for agriculture that requires effective management, typically in the form of lime (calcium carbonate, CaCO 3 ), application. Mid infrared (MIR) spectroscopy methods offer an alternative to conventional laboratory methods, that may enable cost-effective and improved measurement of soil acidity and responses to liming, including detection of small–scale heterogeneity through the profile. Properties of an acidic soil following lime application were measured using both MIR spectroscopy with Partial Least Squares Regression (MIR-PLSR) and laboratory measurements to (a) compare the ability of each method to detect lime treatment effects on acidic soil, and (b) assess effects of the different treatments on selected soil properties. Soil properties including soil pH (in H 2 O and CaCl 2 ), Aluminium (Al, exchangeable and extractable), cation exchange capacity (CEC) and organic carbon (OC) were measured at a single field trial receiving lime treatments differing in rate, source and incorporation. Model performance of MIR-PLSR prediction of the soil properties ranged from R 2 = 0.582, RMSE = 2.023, RPIQ = 2.921 for Al (extractable) to R 2 = 0.881, RMSE = 0.192, RPIQ = 5.729 for OC. MIR-PLSR predictions for pH (in H 2 O and CaCl 2 ) were R 2 = 0.739, RMSE = 0.287, RPIQ = 2.230 and R 2 = 0.788, RMSE = 0.311, RPIQ = 1.897 respectively, and could detect a similar treatment effect compared to laboratory measurements. Treatment effects were not detected for MIR-PLSR-predicted values of CEC and both exchangeable and extractable Al. Findings support MIR-PLSR as a method of measuring soil pH to monitor effects of liming treatments on acidic soil to help inform precision agricultural management strategies, but suggests that some nuance and important information about treatment effects of lime on CEC and Al may be lost. Improvements to prediction model performance should be made to realise the full potential of this approach.

Mathematical vs. machine learning models for particle size distribution in fragile soils of North-Western Himalayas - Owais Bashir; Shabir Ahmad Bangroo; Shahid Shuja Shafai; Tajamul Islam Shah; Shuraik Kader; Lizny Jaufer; Nicola Senesi; Alban Kuriqi; Negar Omidvar; Soora Naresh Kumar; Ayyanadar Arunachalam; Ruby Michael; et al. (Journal of Soils and Sediments, 2024)
Purpose Particle size distribution (PSD) assessment, which affects all physical, chemical, biological, mineralogical, and geological properties of soil, is crucial for maintaining soil sustainability. It plays a vital role in ensuring appropriate land use, fertilizer management, crop selection, and conservation practices, especially in fragile soils such as those of the North-Western Himalayas. Materials and methods In this study, the performance of eleven mathematical and three Machine Learning (ML) models used in the past was compared to investigate PSD modeling of different soils from the North-Western Himalayan region, considering that an appropriate model must fit all PSD data. Results and discussion Our study focuses on the significance of evaluating the goodness of fit in particle size distribution modeling using the coefficient of determination (R 2 adj = 0.79 to 0.45), the Akaike information criterion (AIC = 67 to 184), and the root mean square error (RMSE = 0.01 to 0.09). The Fredlund, Weibull, and Rosin Rammler models exhibited the best fit for all samples, while the performance of the Gompertz, S-Curve, and Van Genutchen models was poor. Of the three ML models tested, the Random Forest model performed the best (R 2 = 0.99), and the SVM model was the lowest (R 2 = 0.95). Thus, the PSD of the soil can be best predicted by ML approaches, especially by the Random Forest model. Conclusion The Fredlund model exhibited the best fit among mathematical models while random forest performed best among the machine learning models. As the number of parameters in the model increased better was the accuracy.

Five years later, with double the demographic data, naked mole-rat mortality rates continue to defy Gompertzian laws by not increasing with age - J. Graham Ruby; Megan Smith; Rochelle Buffenstein (GeroScience, 2024)
The naked mole-rat ( Heterocephalus glaber ) is a mouse-sized rodent species, notable for its eusociality and long lifespan. Previously, we reported that demographic aging, i.e., the exponential increase of mortality hazard that accompanies advancing age in mammals and other organisms, does not occur in naked mole-rats (Ruby et al., 2018), a finding that has potential implications for human healthy aging. The demographic data supporting that conclusion had taken over three decades to accumulate, starting with the original rearing of H. glaber in captivity. This finding was controversial since many of the animals in that study were relatively young. In the 5 years following that study, we have doubled our quantity of demographic data. Here, we re-evaluated our prior conclusions in light of these new data and found them to be not only supported but indeed strengthened. We additionally provided insight into the social dynamics of captive H. glaber with data and analyses of body weight and colony size versus mortality. Finally, we provide a phylogenetically proximal comparator in the form of lifespan data from our Damaraland mole-rat ( Fukomys damarensis ) colony and demographic meta-analysis of those data along with published data from Ansell’s mole-rat ( Fukomys anselli ). We found Fukomys mortality hazard to increase gradually with age, an observation with inferences on the evolution of exceptional lifespan among mole-rats and the ecological factors that may have accompanied that evolution.

Exploring the food-energy-water nexus in coupled natural-human systems under climate change with a fully integrated agent-based modeling framework - Jiaorui Zhang; Y.C. Ethan Yang; Guta W. Abeshu; Hongyi Li; Fengwei Hung; Chung-Yi Lin; L. Ruby Leung (Journal of Hydrology, 2024)

Associations of prenatal ambient air pollution exposures with asthma in middle childhood - Marnie F. Hazlehurst; Kecia N. Carroll; Paul E. Moore; Adam A. Szpiro; Margaret A. Adgent; Logan C. Dearborn; Allison R. Sherris; Christine T. Loftus; Yu Ni; Qi Zhao; Emily S. Barrett; Ruby H.N. Nguyen; et al. (International Journal of Hygiene and Environmental Health, 2024)

Characterization and variability of morpho-genetic traits of commercial importance in achiote collection - Rodolfo Pech-Hoil; Miriam Monserrat Ferrer; Margarita Aguilar-Espinosa; June Simpson; Ruby Valdez-Ojeda; Adolfo Guzmán-Antonio; Luis Carlos Gutiérrez-Pacheco; Renata Rivera-Madrid (New Forests, 2024)

Applications and advancements of nanoparticle-based drug delivery in alleviating lung cancer and chronic obstructive pulmonary disease - Gabriele De Rubis; Keshav Raj Paudel; Leander Corrie; Samir Mehndiratta; Vyoma K. Patel; Popat S. Kumbhar; Arehalli Sidramappa Manjappa; John Disouza; Vandana Patravale; Gaurav Gupta; Bikash Manandhar; Rashi Rajput; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Biotechnological strategies to decipher the functions of abiotic stress-associated genes in soybean - Ruby Tiwari; Manchikatla V. Rajam (Plant Biotechnology Reports, 2024)

Investigating the levels of organochlorine pesticides in human milk at three lactational stages: an intensive Ghanaian study - Justice Wiston Amstrong Jonathan; Daniel Elorm Kwame Kabotso; David Kofi Essumang; John Kwesi Bentum; Innocentia Ruby Gborgblorvor; Fidelis M. Kpodo; Francis Ofosu-Koranteng; Comfort Worna Lotse; Norkplim Dei Hlorlewu (Environmental Monitoring and Assessment, 2024)

Removal of organic micropollutants in biologically active filters: A systematic quantitative review of key influencing factors - Sana Ajaz; Ashraf Aly Hassan; Ruby N. Michael; Frederic D.L. Leusch (Journal of Environmental Management, 2024)

Unconfined fishway design, implementation, and assessment for the emerald Shiner (Notropis atherinoides) in the Upper Niagara River, New York - Jundong Qiao; Sean J. Bennett; Joseph F. Atkinson; Paul A. Cocca; Sarah K. Delavan; Andrew R. Hannes; Bryan A. Hinterberger; Timothy J. Pede; Alicia Pérez-Fuentetaja; Richard J. Ruby (Ecological Engineering, 2024)

Region and cloud regime dependence of parametric sensitivity in E3SM atmosphere model - Yun Qian; Zhun Guo; Vincent E. Larson; L. Ruby Leung; Wuyin Lin; Po-Lun Ma; Hui Wan; Hailong Wang; Heng Xiao; Shaocheng Xie; Ben Yang; Kai Zhang; et al. (Climate Dynamics, 2024)
The Department of Energy (DOE)’s Energy Exascale Earth System Model (E3SM), including its atmosphere model (EAM), has many relatively new features. In a previous study we conducted a systematic parametric sensitivity analysis for EAM based on short, perturbed parameter ensemble (PPE) simulations, mainly focusing on global mean climate features and metrics. While parameter values in global climate models are generally invariant in space and time, model response to parameters perturbation may vary by regions and climate regimes, which motivates the need to better understand the EAM model behaviors and physics at regional scale and process level. In this study, using the same set of PPE simulations and a similar sensitivity analysis framework, we identify parameters that cause largest sensitivities over different regions and compare model responses in fast atmospheric processes to the parameters across different cloud regimes for several important cloud-related fidelity metrics. We find that cloud forcing has opposite response to some parameters over mid-latitude vs. tropical land. We also analyze how the parametric sensitivity varies as stratocumulus transitions to shallow convection and to deep convection over ocean. Low cloud forcing and shortwave cloud forcing in the subtropical eastern Pacific are most sensitive to the parameters controlling the width of the probability density function (PDF) of the subgrid vertical velocity ( w’ ) ( gamma ) and the damping of the w’ skewness ( c8 ) near the coast but become more sensitive to the parameter affecting the damping of the w’ variance ( c1 ) further offshore. Detailed interpretation of the spatial dependence of parametric sensitivity is provided. We also investigate how the parametric sensitivity evolves with prediction duration. This study improves our process-level understanding of cloud physics and parameterization and provides insights for developing more advanced regime-aware parameterization schemes in global climate model.

Acute Toxicity, Hematological Profile, and Histopathological Effects of MgO Nanoparticles on Gills, Muscle, Liver of Mrigal, Cirrhinus mrigala - Shanmugam Sudhabose; Balakrishnan Sooryakanth; Muthuswami Ruby Rajan (Biological Trace Element Research, 2024)

Influence of seasonal variation on steroidal content and in vivo post-coital antifertility activity of bark extracts of Caesalpinia pulcherrima Linn - Benson Mathai Kochikuzhyil; Mansour Almuqbil; Syed Mohammed Basheeruddin Asdaq; Abdul Rahim Huma; Ruby Benson; Kuntal Das; Majeshwar Shrinath Baliga; Subash Philip; Ahmed Alshehri; Adel Alghamdi; Moneer E. Almadani; Farhana Yasmin; et al. (South African Journal of Botany, 2024)

Chloridoideae grass phytoliths can distinguish two different rainfall zones: A case study from northern parts of Western Ghats, India - Manjuree Karmakar; Ranita Biswas; Biswajit Mukherjee; Oindrila Biswas; Madhab Naskar; Dipak Kumar Paruya; Althaf Ahamed Kabeer K; Ruby Ghosh; Subir Bera (Quaternary International, 2024)

A new method for predicting hurricane rapid intensification based on co-occurring environmental parameters - Anushka Narayanan; Karthik Balaguru; Wenwei Xu; L. Ruby Leung (Natural Hazards, 2024)
Tropical cyclones (TCs) that undergo Rapid Intensification (RI) can pose serious socioeconomic threats and can potentially result in major damaging impacts along coastal areas. Considering the complexity of various physical mechanisms that play a role in RI and its relatively low probability of occurrence, predicting RI remains a major operational challenge. In this study, we propose a simple deterministic binary classification model based on the co-occurrence of environmental parameters (MCE) to predict an RI event. More specifically, the model determines the possibility of RI based on a simple count of the number of environmental predictors deemed favorable and unfavorable. We compare our model results to logistic regression (LR) and decision tree (DT) models, well-trained using the same set of environmental predictors. Results reveal that at an RI threshold of 30 kt, the MCE exhibits a critical success index score of 0.233 which is 14% higher than DT and LR model performances. When tested at multiple RI thresholds, the MCE displays relatively higher skill scores across multiple metrics. By simultaneously evaluating the favorability of predictors, the MCE is able to comparatively reduce the number of false alarms predicted when certain predictors are unfavorable toward RI. Interpreting these model results to gain a physical understanding of how co-occurring environmental parameters can affect RI, we highlight future directions for using models based on the MCE approach to understand and predict TC RI as well as other meteorological extremes.